Molecular-based diagnostics, including future trends. (October 2017) - Goldenberg, Simon
Abstract: Microbiological diagnosis has traditionally relied on phenotypic methods involving culture and biochemical testing to identify and characterize clinically relevant pathogens. These techniques have several disadvantages including poor sensitivity and long turn-around time. Molecular and mass spectrometry techniques are rapidly changing infection diagnosis and management of patients. Compared with conventional culture-based techniques, these modern approaches provide substantially more rapid and specific information on organism identification and on the presence of resistance mechanisms. These methods are expected to contribute substantially to enhancing antimicrobial stewardship and to decreasing 'time to appropriate antibiotics', one of the most important factors in improving the prognosis of patients with life-threatening infections. The UK government review on antimicrobial resistance has clearly laid out the real implications of spreading drug resistance, and provides an overview of how rapid diagnostics can play an important role in reducing unnecessary antimicrobial use and/or allowing early antibiotic de-escalation. 1 This article gives an overview of some of the practical applications of these newer technologies.